Systematic review of the automation of business processes’ literature - Tinoco-León, Abilio (2017)
Companies face the challenge of placing a product or service before their competition, and need to respond to their customers’ requirements. For these reasons, its organizational structure is being oriented to an optimization of the business processes. They are required to be agile to respond to the business environment, i.e., customer requirements, as well as new legal provisions and business strategies. The automation of business processes contributes significantly with the agility of these processes. The purpose of this article is to classify the methods used for the automation of business processes. The literary review used articles related to this topic as reference. Therefore, articles were searched in Scopus, Google Scholar and Springer. The review process was carried out in two stages: first, the articles found were filtered based on the reading of the titles, abstracts and keywords; second, articles were selected based on the complete reading of the filtered articles.